Pilgrim theology : core doctrines for Christian disciples - Horton, Michael Scott (Grand Rapids, MI : Zondervan, 2011)
This concise tour of Christian doctrine is an ideal resource for Sunday School, reading groups, church-wide studies, and college courses examining the Christian faith and the Reformed tradition. Based, in part, on Michael Horton's award-winning The Christian Faith, this new study -- Pilgrim Theology -- presents the church's teachings in an accessible manner, while engaging other Christian traditions and contemporary theological issues. - Publisher.
Knowing God -- God's written Word -- The living God -- The Holy Trinity -- Creator-Lord and created servant -- The fall -- The person of Christ -- The work of Christ -- The Spirit and the kingdom -- Chosen and called -- Union with Christ -- Justified and adopted -- Sanctification and perseverance -- The doctrine of glorification -- Word and sacraments -- Baptism and the Supper -- The church -- The end times -- The resurrection of the body and the life everlasting.
Includes bibliographical references and indexes.
Keywords: Theology, Doctrinal; Reformed Church -- Doctrines